2022
DOI: 10.1155/2022/7389658
|View full text |Cite
|
Sign up to set email alerts
|

How Cognitive Reserve should Influence Rehabilitation Choices using Virtual Reality in Parkinson’s Disease

Abstract: Virtual reality (VR) is used in the rehabilitation of patients with Parkinson's disease (PD) in several studies. In VR trials, the motor, physical characteristics, and the degree of the disease are often well de ned, while PD cognitive reserve is not. is systematic review was performed to de ne a cognitive pro le for patients with PD who could best bene t from using VR to enhance functional motor aspects during rehabilitation. PubMed, Cochrane Library, Scopus, and Web of Sciences databases were analysed to ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…While VR is regarded as a support tool for neurological and psychological function in chronic patients out of the operative setting, its potential role in postoperative care requires more research [30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…While VR is regarded as a support tool for neurological and psychological function in chronic patients out of the operative setting, its potential role in postoperative care requires more research [30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies revealed the role of demographics, clinical conditions and psychosocial variables in modulating rehabilitation outcomes [1][2][3][4] . Besides these factors, the latest evidence supported the role of life-long stimulating activities in influencing patients' attitudes and responses to nonpharmacological interventions in neurological disorders [4][5][6][7][8][9][10] . Especially, patients with higher education, higher cognitive commitment to working activities, and spending more time in stimulating leisure activities may rely on greater cognitive and neural reserve during a rehabilitation program.…”
mentioning
confidence: 99%